PARENTING EDUCATION DALAM MENJAGA IMUN PASCA PANDEMI DI DUSUN LENDANG KANTONG DESA SUKAREMA KECAMATAN LENEK - husairi, husairi; Munir, Muhammad; Alwan, Muhammad; Herawati, Nita Sunarya; Hayaturraiyan, Hayaturraiyan; Lisnawati, Lisnawati (Empowerment: Jurnal Pengabdian pada Masyarakat, 2023)
Abstract The Covid-19 pandemic has gradually passed, but people must remain vigilant about the spread of the virus, to reduce the post-pandemic spread of Covid-19, the most important thing to do is to maintain immunity and implementing a healthy lifestyle, especially in the family environment. The parental role is very important to guiding and accompanying every child's growth and development, in the process of maintaining health and implementing a healthy lifestyle, Children need attention and support from parents, so that children can maintain their immunity and health in post-pandemic today. This community service is aims to increase awareness in the community around the family about the importance of implementing a healthy lifestyle in the post-pandemic period, and to provide knowledge to the community on how to live a healthy lifestyle in the family environment. The method of implementing the activity is conducting outreach with a parenting education approach for parents in Sukarema Village. An indicator of the success of this activity is establish of a community that has knowledge and insight regarding a healthy lifestyle and then applies it to their family and surroundings.